Sustainable Meat Production from a Marketing and Management Perspective: a Case Study of Kirsehir Province - Basar Altuntas; Halil Ozcan Ozdemir (Journal of Global Innovations in Agricultural Sciences)
In recent years, a series of reports have been published highlighting the negative environmental impacts of meat production, emphasizing its substantial contribution to greenhouse gas emissions and climate change. Concerns regarding the high-water consumption associated with cattle farming and the environmental issues caused by livestock waste are among the significant barriers to the sustainability of meat production. The primary objective of this study is to conduct a situational analysis aimed at ensuring sustainable beef production and to evaluate the marketing and management strategies of enterprises operating in this field. To achieve this objective, a qualitative study was conducted with producers in Kirsehir. The findings reveal that producers’ local market knowledge, high-quality meat production, and awareness of sustainability stand out as key strengths. In contrast, the lack of integrated facilities, a declining young population, and price volatility were identified as major weaknesses. Key opportunities include the establishment of modern farms, digitalization, and geographical indication labeling. At the same time, climate change, water scarcity, and economic uncertainty pose critical threats. The findings highlight the need for adopting innovative technologies, environmentally friendly practices, and direct-to-consumer distribution channels. Branding, such as the “Kirsehir Beef” label, is crucial, and promoting local products through events can boost regional visibility. Environmental strategies, including reducing carbon footprints, producing biogas, and improving waste management, are also essential. Policymakers, NGOs, and academics must actively engage in promoting sustainable practices and developing strategies that balance environmental and economic goals. Keywords: Food sector, sustainable solutions, food security, environmental concerns, meat consumption, SWOT analysis